Diet quality determinants among manufacturing workers in Brazil: Socio-demographic factors, food choices, and ultra-processed foods - Anissa Melo Souza; Karina Gomes Torres; Raiane Medeiros Costa; Gabriela Santana Pereira; Célia Márcia Medeiros Morais; Antonio Gouveia Oliveira; Ingrid Wilza Leal Bezerra (PLoS ONE, 2026)
This study evaluated the association between diet quality and socio-demographic factors, anthropometric measures, food choices, and consumption of processed foods in a low-income Brazilian manufacturing worker population, addressing gaps in evidence from low- and middle-income countries (LMICs). A cross-sectional study was conducted with 921 workers from 33 industries in Rio Grande do Norte, Brazil, selected via stratified proportional and multi-stage sampling. Diet quality was assessed using the Diet Quality Index-International (DQI-I), which evaluates variety, adequacy, moderation, and balance. Dietary intake was measured via 24-hour recalls, and foods were classified by processing level (NOVA system). Socio-demographic, anthropometric, and food choice data (using the Food Choice Questionnaire) were collected. Associations were analyzed using multilevel linear regression. Higher diet quality was associated with being male (p = 0.001). Among women, diet quality improved with age (p = 0.018) and participation in a food assistance program (p < 0.001), whereas those variables showed no association among men. Prioritizing natural food content predicted higher DQI-I scores in both sexes (p < 0.05), while weight control was significant only for women (p = 0.034). Unprocessed food intake showed a positive association (p < 0.001) with diet quality, whereas ultra-processed food consumption was inversely associated (p < 0.001), most notably with diet variety and adequacy in both sexes, and with moderation in women. Food choices also influence diet quality, with people who value health benefits, natural content, weight control, and familiar products being more likely to consume diets with better variety and adequacy. No significant associations were found between diet quality and anthropometric measures. Socio-demographic factors, food choices, and levels of food processing significantly influence diet quality in this low-income Brazilian population. Public health strategies targeting reductions in ultra-processed food consumption and supporting food assistance programs may improve dietary patterns, particularly among women. These findings highlight the need for context-specific interventions to address nutrition transitions in LMICs.